2013
DOI: 10.1177/193229681300700112
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fasting Blood Test for Insulin Resistance and Prediabetes

Abstract: Background: Insulin resistance (IR) can precede the dysglycemic states of prediabetes and type 2 diabetes mellitus (T2DM) by a number of years and is an early marker of risk for metabolic and cardiovascular disease. There is an unmet need for a simple method to measure IR that can be used for routine screening, prospective study, risk assessment, and therapeutic monitoring. We have reported several metabolites whose fasting plasma levels correlated with insulin sensitivity. These metabolites were used in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 54 publications
2
87
0
11
Order By: Relevance
“…We previously reported that a-HB, L-GPC, and oleic acid are biomarkers of insulin sensitivity as measured by the hyperinsulinemic-euglycemic clamp in the RISC study at baseline (25,29). In a subsequent report, we showed that a-HB and L-GPC were predictors of incident dysglycemia in RISC and of incident T2DM in Botnia (13).…”
Section: Discussionmentioning
confidence: 80%
“…We previously reported that a-HB, L-GPC, and oleic acid are biomarkers of insulin sensitivity as measured by the hyperinsulinemic-euglycemic clamp in the RISC study at baseline (25,29). In a subsequent report, we showed that a-HB and L-GPC were predictors of incident dysglycemia in RISC and of incident T2DM in Botnia (13).…”
Section: Discussionmentioning
confidence: 80%
“…These models have been said to be quite simple and require only a single blood sample, but their advantages over fasting insulin are not clear. The other models that are based on the oral glucose tolerance test (OGTT), using various combinations of glucose and insulin values from the fasting state and during the OGTT include the Matsuda index, the Stumvoll index and oral glucose insulin sensitivity, as was identified by Cobb et al 82 More complex methods, including insulin tolerance test and the frequently sampled intravenous glucose tolerance test, require multiple blood samples and thus are complicated and not practical for routine screening purposes. Therefore, there remains a need for a simple IR test for routine screening, prospective studies, risk assessment and therapeutic monitoring.…”
Section: Fasting Blood Insulin Homeostasis Model Assessment Of Insulmentioning
confidence: 99%
“…Obesity is closely linked to IR, with BMI and waist circumference being good predictors of IR. 82 However, a number of models, including HOMA-IR, quantitative insulin sensitivity check index and fasting IR index, were proposed as more simplified measures of insulin sensitivity. 82 Other related models use fasting insulin plus various lipids measures, such as free fatty acids (elevated), triglycerides (elevated) or high-density lipoprotein and/or total cholesterol (elevated).…”
Section: Fasting Blood Insulin Homeostasis Model Assessment Of Insulmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, α-HB was established as a marker of IR (5). α-HB is derived from α-ketobutyrate and has the potential to identify risk of impairment of glycemic control and conversion of prediabetes to an evident diabetic state (6,7).…”
mentioning
confidence: 99%